Identifikasi Lalat Buah (Bactrocera spp) Di Chili, Bitter Melon, Jambu Dan Jambu Bol Di Kota Ambon - Tariyani Tariyani; John A Patty; Victor G Siahaya (Agrologia, 2013)
Fruit flies (Diptera: Tephritidae) are important pests of horticultural crops with the intensity of their attacks can achieve 100%.  The control by quarantine regulations and the use of attractants will be more successful when the information about the species that attack horticultural crops has been known clearly. This study aimed to identify the species of fruit fly that attack pepper (Capsicum annum), bitter melon, guava and guava bol and to know the number and sex ratio of fruit fly pests. The method used was the survey methods, by taking/collecting pepper, bitter melon, guava and guava bol which contained fruit fly attack symptoms, maintained until it was discovered in the imago, later it was identified. Based on the results of the study, we found that fruit flies that attack the chili was B. papaya, in bitter melon was B. cucurbitae, in bool guava fruit and guava was B. Albistrigata. The number of fruit flies in chili was 21, in bitter melon was176, 89 in bol guava, and in guava was 90. Sex ratio in chili fruit flies (1:1), bitter melon (1:1), guava bol (1:1) and guava (2:1).